Studies on sound and carious enamel with the quantitative acoustic microscope. - Peck, S; Rowe, J; Briggs, G (1989)
The scanning acoustic microscope gives strong contrast from small caries lesions in sections of human enamel. The uniqueness of the acoustic microscope lies in its ability to image elastic properties. In addition to revealing the extent and the shape of lesions, the microscope may also be used to measure the elastic properties point by point across an area of interest. Since enamel is anisotropic, measurements of the Rayleigh velocity and attenuation were made as a function of direction on a section of sound enamel. The velocity was greatest parallel to the prism axis, and the attenuation was least in this direction. Measurements of V(z) across a section through a lesion are presented. The variation of attenuation can be interpreted in terms of the development of demineralization, initially along prism boundaries and then along cross-striations. The variation of velocity indicates a substantial reduction of elastic stiffness in the lesion.